Radio frequency circuit design - Davis, W. Alan (Wiley series in microwave and optical engineering, 2011)
"Radio Frequence (RF) design techniques and applications have greatly expanded over the past decade. This Second Edition of Radio Frequency Circuit Design has been thoroughly updated to cover the latest developments in RF communications, giving practicing engineers and students authoritative guidance in contemporary design and analysis of RF circuit components. This new edition features clear, step-by-step demonstrations of new design techniques for RF circuits, including phase locked loops, filters, transformers, amplifiers, mixers, and oscillators. It offers a better understanding of RF power amplifiers and expands upon class D and E power amplifier treatment. Also increased coverage is given to oscillator phase noise and impedance matching. The book includes real-life examples illustrating the role of the described techniques in the overall design of various RF communication systems; additional features include solenoid design and double-tuned matching circuit examples, transistor and amplifier formulas, transformed frequency domain measurements, and analytical spiral inductor model references."--Publisher's description.